The Corrective Effect of Factor VIII-coated Red Blood Cells in Haemophilic Plasma with Antibodies to Factor VIII - Uszyński, Leszek (Thrombosis and Haemostasis, 1974)
Factor VIII-coated red blood cells had an evident corrective effect on plasma of haemophiliacs with inhibitors. This effect was especially significant when tanned coated red cells were used. The direct coating of washed red blood cells by factor VIII concentrates is also feasible. The results were better with fraction C-I (AHG concentrate containing dextran) than with fibrinogen-free concentrate. It seems that dextran enhances the attachment of factor VIII to human erythrocytes. In the direct coating-procedure the time of incubation was important, but temperature and pH were not critical. The results obtained indicate that factor VIII attached to red blood cells is more resistant to inhibitors than factor VIII in solution.The possibility of using factor VIII-coated red cells for the management of patients with antibodies to factor VIII is discussed.